RANCANG BANGUN SISTEM INFORMASI INVENTORY MENGGUNAKAN METODE RAPID APPLICATION DEVELOPMENT (RAD) PADA TOKO ABADI JAYA - Shabtina, Putri Hadeya; Sabila Zharfa; Pratama, Arya Safta; Arribe, Edo (JURNAL ILMIAH INFORMATIKA, 2024)
Toko Abadi Jaya is a trading company in the furniture industry that uses technology to enhance its operations. The company recognizes the importance of technology in accessing fast and accurate information to solve various challenges. Currently, many manual tasks, such as marketing, finance, administration products management, and checking product stock availability can take a lot of time and accuracy. For example, employees need to call other employees in the inventory warehouse to inquire about stock availability. This process hinders efficiency and effectiveness. To resolve this issue, the company has developed an application-based inventory information system. This system enables employees to quickly check the availability of goods without wasting time. The application also generates reports, which aid the owner in decision-making. Therefore, it is necessary to have carefully organized data stored in the database so that the work process is easy in making reports. The design of this application uses the Rapid Application Development (RAD) method and the Unified Modeling Language (UML) design model, with Visual Studio Code as the text editor tool and Laravel as the PHP framework. This aims to facilitate the process of monitoring the stock of incoming goods and outgoing goods and provide benefits to the work process of inputting inventory of goods and providing precise and accurate reports at Toko Abadi Jaya.